ANALISA ASPEK KEAMANAN DAN KERAHASIAAN DOKUMEN REKAM MEDIS DI RUANG FILING RUMAH SAKIT VINA ESTETICA - BR KABAN, PEBERIWATI (JURNAL ILMIAH MAKSITEK, 2023)
A medical Document (DRM) is a tool to record the transactions, Quality of service can be enhanced when supported by the safety and confidentiality of medical record patient in the storage room. Security and confidentiality of medical records in RS Vina Estetica were still not going well. Still found leaking roof space of filing, humid shelving, dusty, absence of camphor, the door is often not locked, and still found the patient requests their own medical record and bring the document it self, and document medical records piled up on the floor. The main problems were the lack of procedures of security and confidentiality of medical records. Therefore, the researcher wanted to describe aspects of security and confidentiality of the medical record documents on filing unit in RS Vina Estetica. This study used a descriptive, cross-sectional approach and methods were observation and interviews. Subjects were filing officers, as many as five people, and object was the security and confidentiality of medical records in Filing. The research instrument used were guidelines for observation, interviewsand gauging the temperature of the moisture. Data processing is editing, tabulation, and data presentation. Based on the observation of security medical records processing in filing RS Vina Estetica, it can be seen from the physical aspect was still not safe from the dangers of fire and flood, in terms of biological not using camphor on each shelf, and in terms of chemical officers were still doing activities such as eating and drinking in the filing room. From the aspect of confidentiality, unlocked door and patients or staff other than medical record personnel enter the filing room. There were no policies or standard operating procedures governing the security and confidentiality of medical records. To maintain the security and confidentiality of medical records, it needs facilities and infrastructure and the rooms were quite safe and good for maintaining confidentiality medical records. Policies and procedures need to be made that contain rules in providing good service.